Gambaran Resiliensi Keluarga dengan Anak Cerebral Palsy: A Systematic Literature Review - Izzati Nuraisya Kurniasari; Shafiyya Rahma Khoerunnisa; Gezi Salsa Bila; Ludfiah Azahra; Ahmad Zaky Maulana Putra; Rahmadianti Aulia (CV. ITTC INDONESIA, 2026)
The presence of a child with cerebral palsy presents various psychological, social, economic, and caregiving challenges that may affect family functioning. Nevertheless, many families are able to adapt and maintain their well-being through the development of family resilience. This study aimed to describe family resilience among families of children with cerebral palsy using a Systematic Literature Review (SLR) approach. Articles were retrieved from Semantic Scholar, Garuda, and DOAJ databases following the PRISMA guidelines. Studies published between 2017 and 2026 were selected based on predetermined inclusion and exclusion criteria. Of the 253 articles initially identified, 11 studies met the eligibility criteria and were included in the review. The findings indicate that family resilience is a dynamic adaptation process in coping with the long-term demands of caregiving. Internal factors contributing to resilience include acceptance of the child's condition, effective family communication, optimism, and adaptive coping strategies. External factors include social support, institutional support, socioeconomic conditions, and religiosity. Strong family resilience is associated with improved quality of life, healthier family functioning, and better psychological well-being among parents. These findings highlight the importance of strengthening family resilience as a foundation for developing psychological interventions and family support programs for families raising children with cerebral palsy.